Fluorescent sophorolipid molecular assembly and its magnetic nanoparticle loading: a pulsed laser process - Singh, Pradeep Kumar; Mukherji, Ruchira; Joshi-Navare, Kasturi; Banerjee, Abhik; Gokhale, Rohan; Nagane, Satyawan; Prabhune, Asmita; Ogale, Satishchandra (Green Chemistry, 2013)
We report realization of strong green fluorescence in a fully biocompatible highly spherical mesoscale molecular assembly of sophorolipid created by pulsed UV laser processing of a water-based dispersion of sophorolipid. Remarkably, the said fluorescence is totally absent in the original molecule of sophorolipid and is thus the property of the pulsed laser induced modifications in the molecule and the assembly. We have separately examined the consequences of laser irradiation for glucose and oleic acid components which form the sophorolipid. This fluorescence character appears to be driven by the oleic acid component while the assembly process is assisted by the glucose component. Importantly the laser synthesized mesostructures can be easily redispersed in an aqueous medium after being dried and can also be loaded with magnetic nanoparticles (magnetite) for inducing the hyperthermia effect.

From micron to nano-curcumin by sophorolipid co-processing: highly enhanced bioavailability, fluorescence, and anti-cancer efficacy - Singh, Pradeep Kumar; Wani, Kirtee; Kaul-Ghanekar, Ruchika; Prabhune, Asmita; Ogale, Satishchandra (RSC Advances, 2014)
Co-sonication of curcumin and acidic sophorolipid in aqueous solution is shown to lead to a dramatic enhancement of curcumin bioavailability through size reduction and encapsulation. The interaction between the two is studied and discussed based on optical absorption, photoluminescence, dynamic light scattering (DLS), zeta potential, FE-SEM, TEM, Infrared spectroscopy and X-ray diffraction measurements. The cytotoxicity effects of curcumin on breast cancer cell lines, MCF-7 and MDA-MB-231, are shown to be significantly enhanced by the formation of its complex with sophorolipid. The relative cytotoxicity of curcumin with its SL(A) complex is more due to the presence of the glucose moiety. The results further suggest that sophorolipid based formulations, which solubilize and nano-encapsulate curcumin after lipid digestion, show great potential for curcumin cell entry.

New yeast isolate Pichia caribbica synthesizes xylolipid biosurfactant with enhanced functionality - Joshi-Navare, Kasturi; Singh, Pradeep Kumar; Prabhune, Asmita (European Journal of Lipid Science and Technology, 2014)
Sophorolipids (SL) belong to a class of glycolipidic biosurfactants suitable for a wide range of applications. The structural diversity in SL gives rise to variation in physicochemical and biological properties. To achieve the less explored head group diversity in sophorolipid structure, a new xylose fermenting yeast Pichia caribbica has been employed for biosurfactant production. The media and fermentation parameters have been optimized to achieve maximum yield of 7.48 g/L. The physicochemical properties of the xylolipid biosurfactant have been assessed. It reduced the surface tension of distilled water from 70 to 35.9 mN/m with the low critical micellar concentration (CMC) 1.0 mg/L as compared to typical SL (reported CMC range 40-100 mg/L). Structural characterization was done using FTIR and HR-MS to identify the structure. 17-L-[(beta-D-xylopyranosyl)-oxy]-Delta 9-heptadecanoic acid correlated to m/z 415 majorly constituted the product. Control experiment was performed in which glucose was provided as the hydrophilic carbon. This product was also subjected to HR-MS analysis to determine its chemical nature and found to be different from xylolipid. Presence of xylose as head group was anticipated to give altered physicochemical and biological activities and indeed a low CMC value and better inhibitory action was demonstrated against Staphylococcus aureus. Practical applications: Sophorolipids produced by microbial sources have several advantageous properties over commercial petroleum-based surfactants including biodegradability, environmentally friendly nature, and low toxicity. Here, we have attempted to modify the hydrophilic head group by incorporating xylose in place of glucose. This molecule will also behave differently in response to different stimuli. Stimuli-responsive surfactants are a class of compounds with applications in stabilization of emulsions, suspensions or foams, drug encapsulation and delivery, hard-surface cleaning, personal care applications.
Keywords: Antibacterial action; Critical micelle concentration; Pichia caribbica; Sophorolipid; Xylolipid

From micron to nano-curcumin by sophorolipid co-processing: highly enhanced bioavailability, fluorescence, and anti-cancer efficacy (vol 4, pg 60334, 2014) - Singh, Pradeep Kumar; Wani, Kirtee; Kaul-Ghanekar, Ruchika; Prabhune, Asmita; Ogale, Satishchandra (RSC Advances, 2015)

Pulsed laser-driven molecular self-assembly of cephalexin: aggregation-induced fluorescence and its utility as a mercury ion sensor - Singh, Pradeep Kumar; Prabhune, Asmita; Ogale, Satishchandra (Photochemistry and Photobiology, 2015)
A fluorescent self-assembly of cephalexin is obtained by pulsed laser irradiation process. An intense fluorescence emission is found in the self-assembled form due to occurrence of a typical aggregation-induced emission in cephalexin molecules. It is observed that fluorescence quenching of the self-assembled fluorescent nanostructures occurs in the presence of extremely low Hg++ ions concentrations (10(-7) M) as compared to other heavy metal ions e.g. Ferrous (Fe++), Manganese (Mn++), Magnesium (Mg++), Cobalt (Co++), Nickel (Ni++) and Zinc (Zn++) at the same concentrations.

UV-assisted size sampling and antibacterial screening of lantana camara leaf extract synthesized silver nanoparticles - Singh, Pradeep Kumar; Bhardwaj, Kirti; Dubey, Parul; Prabhune, Asmita (RSC Advances, 2015)
Green route synthesized silver nanoparticles are extremely toxic to multidrug resistant bacteria and have widespread applications in biomedical science. If the silver reducing weed extract possesses antimicrobial properties then it can additionally contribute to the medicinal activity. Herein, we present a synthesis of silver nanoparticles by using the weed plant Lantana camara's leaf extract. This study shows an easy, quick and cost-effective route to silver nanoparticle synthesis. Size controlled synthesis of Ag-0 nanoparticles is studied and discussed based on optical absorption, photoluminescence, dynamic light scattering (DLS), zeta potential, infrared spectroscopy, X-ray diffraction measurements, FE-SEM and TEM analysis. The synthesis of silver nanoparticles via this green approach shows very high antibacterial activity against E coli (Gram -ve) and S. aureus (Gram +ve) bacteria at a very low concentration (50 ppm Ag nanoparticles). Use of such eco-friendly nanoparticles may open a door for a new range of bactericidal agents.